Analysis and optimization of turned surfaces of AISI 1060 using ANOVA and regression - Chowdhury, M. A.; Debnath, U. K.; Kamruzzaman, M.; Nuruzzaman, D. M.; Mia, Md. Shahin (Faculty of Engineering, University of Kragujevac, 2019)
AISI 1060 carbon steel for turning process is used to find out best cutting parameters using Analysis of Variance (ANOVA) and Regression Concept. Optimization of cutting parameters in turning operation is analyzed in this study. Cutting speed and force affects remarkably on the roughness on the surfaces of the test sample at all cutting operations. The reasonable surface roughness was obtained at a low feed rate in the combination of high cutting speed. Tool vibration was increased with the depth of cut and feed rate. In this study surface roughness was obtained which mostly dependent on the cutting speed, that contribution was 59.74 % and feed rate contribution was found as 13.75 %. The A multilinear regression model was developed to correlate the different cutting parameters.